2009
DOI: 10.1371/journal.pone.0008055
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ Regulates Trophoblast Proliferation and Promotes Labyrinthine Trilineage Differentiation

Abstract: BackgroundAbnormal trophoblast differentiation and function is the basis of many placenta-based pregnancy disorders, including pre-eclampsia and fetal growth restriction. PPARγ, a ligand-activated nuclear receptor, plays essential roles in placental development; null murine embryos die at midgestation due to abnormalities in all placental layers, in particular, small labyrinth and expanded giant cell layer. Previous studies have focused mostly on the role of PPARγ in trophoblast invasion. Based on the previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(123 citation statements)
references
References 31 publications
6
109
3
2
Order By: Relevance
“…Collectively, these data outline a unique mechanism where gemfibrozil, a known activator of PPAR␣, and ATRA, an agonist of RXR␣, together can up-regulate TFEB in brain cells via the PPAR␣/ RXR␣ heterodimer. Although one study reported that PPAR␥-null trophoblast stem cells have lower levels of TFEB on day 4 of differentiation, our study using GW9662, a potent and known PPAR␥ antagonist, did not reveal any substantial involvement of PPAR␥ (31). This could possibly be due to variation in cell types, i.e.…”
Section: Discussioncontrasting
confidence: 74%
“…Collectively, these data outline a unique mechanism where gemfibrozil, a known activator of PPAR␣, and ATRA, an agonist of RXR␣, together can up-regulate TFEB in brain cells via the PPAR␣/ RXR␣ heterodimer. Although one study reported that PPAR␥-null trophoblast stem cells have lower levels of TFEB on day 4 of differentiation, our study using GW9662, a potent and known PPAR␥ antagonist, did not reveal any substantial involvement of PPAR␥ (31). This could possibly be due to variation in cell types, i.e.…”
Section: Discussioncontrasting
confidence: 74%
“…4 PPAR-␥ plays a predominant role in normal vascular function 5 and in the differentiation of labyrinthine trophoblast lineages, 6 which, along with the fetal endothelium, form the vascular exchange interface with maternal blood. 7 A reduction in the placental expression of PPAR-␥ activators has been demonstrated in some women who develop severe preeclampsia, 8 and significantly higher PPAR-␥ DNA binding activity has been demonstrated in placentas from women with both intrauterine growth restriction and preeclampsia. 9 To investigate the role of PPAR-␥ as a potential therapeutic target for preeclampsia, we administered the PPAR-␥ agonist, rosiglitazone, to rats that had undergone reduced uterine perfusion pressure (RUPP) surgery.…”
mentioning
confidence: 99%
“…Further, inclusion of the saturated animal fat (lard) in the diet induced prostatic enlargement and changed the expression of androgen receptor and peroxysome proliferator activated receptor (PPAR ) (Escobar et al, 2009). Polyunsaturated FAs are ligands for the PPAR , which is involved in the regulation of cell differentiation and proliferation (Morales-Garcia et al, 2011;Parast et al, 2009), and therefore appears to represent a possible link between diet and prostatic growth (Escobar et al, 2009). Prostatic atrophy and increased apoptosis in the hypoinsulinemic rats (induced by selective -cell toxins, either streptozotocin or alloxan) further supports the view that insulin plays a central role in the prostatic growth and development (Arcolino et al, 2010;Ikeda et al, 2000;Suthagar et al, 2009;Vikram et al, 2008;Yono et al, 2008;Yono et al, 2005).…”
Section: Evidence From In-vivo Experimentsmentioning
confidence: 80%